Hong–Ou–Mandel control through spectral shaping. (18th July 2018) - Gianani, Ilaria; Polino, Emanuele; Sbroscia, Marco; Rab, Adil S; Roccia, Emanuele; Mancino, Luca; Spagnolo, Nicoló; Barbieri, Marco; Sciarrino, Fabio
Abstract: Since its initial discovery, Hong–Ou–Mandel (HOM) interference has been a key tool in quantum-optical experiments, being at the basis of several quantum technology applications as well as being a relevant characterisation method for the quality of single photon sources. In the context of quantum interferometry, further applications can be enabled by improving the capability of tailoring such effect. Here, we report a proof-of-principle experiment on a novel HOM control approach, based on spectrally shaping photons generated by parametric down conversion sources. By means of a pulse shaper operating on the pump beam in the Fourier plane, selected frequencies can be cut off from the down conversion process, therefore shaping the HOM interference profile. We finally discuss the obtained results towards employing the method for practical application in interferometry.